2018
DOI: 10.1111/jvim.15246
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of point‐of‐care thoracic ultrasound and NT‐proBNP for the diagnosis of congestive heart failure in cats with respiratory distress

Abstract: BackgroundThe diagnosis of congestive heart failure (CHF) in cats is challenging. Point‐of‐care (POC) thoracic ultrasound and NT‐proBNP testing are emerging tools that may aid in diagnosis.Hypothesis/ObjectivesTo assess the diagnostic accuracy of POC lung ultrasound (LUS), focused cardiac ultrasound (FCU), and NT‐proBNP in predicting a final diagnosis of CHF.AnimalsFifty‐one cats in respiratory distress.MethodsBlood NT‐proBNP, LUS, and FCU evaluating left atrial (LA) size and presence of pericardial effusion (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
75
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 40 publications
0
75
0
1
Order By: Relevance
“…In contrast to dogs, the radiographic pattern associated with cardiogenic pulmonary edema in cats is highly variable . A combination of physical examination, point‐of‐care ultrasound examination and point‐of‐care NT‐proBNP often can be helpful when deciding if CHF is the cause of respiratory distress (LOE high) …”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to dogs, the radiographic pattern associated with cardiogenic pulmonary edema in cats is highly variable . A combination of physical examination, point‐of‐care ultrasound examination and point‐of‐care NT‐proBNP often can be helpful when deciding if CHF is the cause of respiratory distress (LOE high) …”
Section: Diagnosismentioning
confidence: 99%
“…The quantitative feline‐specific NT‐proBNP assay using plasma or pleural fluid has good diagnostic accuracy for discriminating between cats with cardiac and noncardiac causes of respiratory distress (LOE high), but it is not recommended for guiding therapeutic decision‐making in cats with respiratory distress because of the delay in receiving test results from an external laboratory. Instead, a point‐of‐care NT‐proBNP assay provides rapid results while maintaining reasonable diagnostic accuracy in discriminating between cardiac and noncardiac causes of respiratory distress, and should be considered when point‐of‐care ultrasound examination is not available (LOE medium) . The point‐of‐care assay can be used on plasma or pleural fluid, the latter diluted 1:1 with saline for greater specificity …”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In both human patients and in veterinary species in the emergency room setting, focused assessment with sonography for trauma, triage, and tracking protocols help diagnose certain conditions, including cavitary effusions, pleural space disease, and pulmonary disease . Focused cardiac ultrasound is useful for differentiating congestive heart failure from non‐cardiac causes of dyspnea in cats . The FCU in the present study is distinct from previously described sonographic protocols due to its use in nonemergent clinical scenarios and its concentration on specific heart structures visualized from a limited number of acquired images …”
Section: Introductionmentioning
confidence: 99%
“…It is well recognized that cats with structural heart disease that is predominately phenotypically left-sided can develop either pulmonary edema, pleural effusion, or both. A number of studies have reported the relative frequency of different manifestations of CHF in cats,[30][31][32] reporting incidence of pleural effusion between 51% and 79% and…”
mentioning
confidence: 99%